Study of clinical spectrum and risk factors of neonatal candidemia - Rahul Gopichand Wadile; Viraj Madhusudan Bhate (Wolters Kluwer Medknow Publications, 2015)
Context: Candida colonization in neonates results in significant morbidity and mortality. The prevalence and clinical significance of neonatal candidemia are poorly understood. Aims: This study aimed to study clinical spectrum and risk factors of neonatal candidemia. Settings and Methods: 108 cases of septicemia were studied. Blood samples were collected into Glucose broth and Bile broth, which are inoculated on Blood agar and MacConkey's agar and incubated at 37° C for 7 days. Candida species were isolated were confirmed by standard techniques. Statistical Analysis Used: The data was collected and analyzed using by using SPSS IBM Company, Chicago, Version 16.0. Results: 62 newborn patients who had a positive Candida blood culture. 47 (79.03%) were low birth weight and 37 (59.67%) were male. 19 (30.65%) were died. Candida species was a contributory factor to mortality in 14 (73.68%) patients. Among Candida isolates, Candida albicans was the commonest (65%) followed by Candida parapsilosis (15%) and Candida glabrata (10%). The risk factors like intrapartum use of antibiotics, vaginal delivery, low birth weight are identified in culture positive neonates. Conclusions: Candida species are assuming an increasing role in nosocomial infections in neonates and is associated with an increased risk of mortality.